Lectotypification of six names of species of Scabiosa s.l. (Caprifoliaceae) endemic to North Africa and related taxonomic notes (ERRATUM) - Barone, Giulio; El Mokni, Ridha; Di Gristina, Emilio; Domina, Gianniantonio (Phytotaxa, 2020)
ERRATUM